Implementasi Penemuan Kasus TB di Puskesmas Sikumana Kota Kupang - Priska Agustina W. Thegu; Serlie K.A. Littik; Rina Waty Sirait (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Tuberculosis (TB) remains a global health problem and is a leading cause of death from infectious diseases. At the local level, TB cases at the Sikumana Community Health Center in Kupang City have fluctuated, with 134 cases in 2022, increasing to 150 cases in 2023, then declining to 147 cases in 2024 and 133 cases in 2025. This situation highlights the need to strengthen TB case finding efforts in primary healthcare facilities to support TB control. This study aims to analyze the implementation of TB case finding at the Sikumana Community Health Center in Kupang City based on aspects of communication, resources, disposition, and bureaucratic structure. This study used a qualitative method with a descriptive approach. Six informants were selected purposively. Data were collected through in-depth interviews and documentation, then analyzed thematically. The results indicate that the implementation of TB case finding at the Sikumana Community Health Center has been quite successful. Policy communication was implemented through outreach and education, supporting the understanding of program implementers. While resources in the form of facilities and infrastructure are adequate, the number of health workers remains limited, resulting in suboptimal active case detection. The disposition of health workers demonstrates commitment and adherence to standard operating procedures (SOPs). The bureaucratic structure is supported by clear SOPs and service flows, but community participation in active screening remains low, resulting in suboptimal case detection. It was concluded that the implementation of TB case detection at the Sikumana Community Health Center has been quite successful, but human resources and community involvement are needed through increased active case detection, expanded door-to-door screening, and strengthened coordination with sub-districts, health workers, and the community.